Association between the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and mortality in patients with metabolic dysfunction-associated steatotic liver disease (MASLD): data from the NHANES III (1988–1994) - Ying Zhang; Peng-Yu Luo; Yu-Na Tang; Jing Wang; Shuai Gao; Yu-Chen Fan; Kai Wang (Nutrition & Metabolism)
Abstract Background The prognostic value of the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) in patients with metabolic dysfunction-associated steatotic liver disease (MASLD) remains unclear. This study aimed to evaluate the associations between the NHHR and all-cause and cause-specific mortality in patients with MASLD. Methods Data for this study were obtained from the National Health and Nutrition Examination Survey (NHANES III and the National Death Index (NDI). The NHHR was calculated according to the formula. The results of mortality associated with the NDI were recorded as of December 31, 2019. We used a multivariate Cox proportional hazard model and restricted cubic spline (RCS) regression to assess the associations between the NHHR and all-cause and cause-specific mortality. In addition, subgroup analyses were performed to explore the relationships between the NHHR and all-cause and cause-specific mortality. Results This study included 3155 patients with a definite diagnosis of MASLD. A total of 1,381 (43.8%) patients with MASLD died, and 1,774 (56.2%) survived. Multivariate Cox proportional hazards model analysis showed that NHHR was not significantly associated with all-cause mortality in MASLD patients. The RCS curve showed a significant nonlinear trend between the NHHR and all-cause mortality in patients with MASLD. Subgroup analysis revealed that the NHHR was better suited to predict cardiovascular mortality in patients without advanced fibrosis. Conclusions Our study revealed the clinical value of the NHHR in the prediction of mortality in the MASLD population. The NHHR can be used as a biomarker for follow-up in people without advanced fibrosis.